Dynamics of near-surface atmospheric stability with implications for land-atmosphere interactions in complex terrain and heterogeneous landscapes (2020)
ABSTRACT: In this work three case studies are used to investigate the influence of atmospheric stability and land cover heterogeneity or transformation on land-atmosphere interactions in two different environments: urban valleys and a tropical forest. The work on urban valleys mainly focuses on the mechanisms of air pollution transport, which are studied using high-resolution numerical simulations. In the forest case, observed data is analyzed to study the dynamics of thermal stratification in a forest site and its contrast with a nearby cropland site. The first study evaluates how urban heat island (UHI) mitigation affects air quality in an idealized urban valley by means of large-eddy simulations. A passive tracer represents air pollution transport in three UHI mitigation scenarios and under two initial stability conditions. Contrary to the common premise, results demonstrate that UHI mitigation can worsen air quality in urban valleys, via the alteration of the mechanisms of air pollution transport. Results also show the theoretical possibility of finding moderate UHI mitigation strategies in which UHI is reduced while limiting the impacts on air quality. A fundamental implication is that these strategies should be explored through case-specific realistic simulations for guiding decision-making in real systems. Large and often expensive urban transformations should not be accomplished under the generalized assumption that UHI mitigation improves environmental quality. This study contributes to building a more general understanding of the potential impacts of UHI mitigation, as well as of the mechanisms behind, which is a continuing challenge with important implications for urban management and planning. The second study examines the dispersion of traffic emissions in the Aburra valley (located in the Colombian Andes) during an episode of severe air pollution, using the WRF-Chem and a Lagrangian model at sub-kilometer resolution. The study focuses on the identification of areas with relatively large carbon monoxide (CO) concentrations, and analyze the role of local and regional air flows in the distribution of pollutants inside the valley. The meteorological model performance, considering different planetary boundary layer parameterizations and grid sizes, is evaluated using available observations. Overall, the meteorological model performance is within recommended benchmarks for complex terrain. Model performance improves with increasing grid resolution for surface temperature and wind direction, but not for wind speed. Both dispersion models reproduce important features of the spatial and diurnal variability of CO in the valley, but underestimate CO concentrations throughout the simulation period. The south and southeast areas of the valley present relatively large CO concentrations, associated to a prevalent northerly transport along the valley axis and reduced transport on the eastern slope. The representation of CO improves when the model adequately reproduces observed rainfall, due to its effects on boundary layer height and stability, which condition ventilation. This study contributes to the research on atmospheric modelling of transport processes in complex terrain, which is crucial for informing decisions on air quality management in critical areas such as urban valleys. The third study investigates the diurnal and seasonal dynamics of vertical temperature profiles in a dense Amazon forest, as well as a comparison of these dynamics between forested and non-forested landscapes. This is achieved through a comparative analysis using two meteorological towers, one located in a primary forest and the other in a neighboring agricultural site. Results show that thermal stratification within the forest canopy can be divided in three profile types. During the daytime, the forest is characterized by a below-canopy temperature inversion (stably stratified) and neutral or unstable conditions above-canopy. At night, the situation is reversed with near neutral conditions in the lower layers and a stable atmosphere starting either within canopy or above the canopy top. This diurnal oscillation occurs almost simultaneously and with opposite behaviors below- and above-canopy, with temperature gradients switching signs around 06 and 18 local time. The dry season results in stronger and more persistent daytime below-canopy inversions, and a nighttime inversion with larger gradients and starting within canopy (instead of above). The thermal stratification near the forest surface is mostly unaffected from the turbulence above the canopy top. In contrast to forest, the cropland site is characterized by mostly unstable conditions during the day and a temperature inversion during the night. These results provide new insights on the dynamics of thermal stratification within forest canopies and could be useful for model-based studies on land-atmosphere interactions and forest loss impacts. Overall, this dissertation provides new evidence about how land heterogeneity, including pronounced elevation gradients in valleys and contrast between urban and rural land or forest and cropland landscapes, affect land-atmosphere interactions through effects on near-ground atmospheric stability. This has important implications for the transport of air pollutants in urban valleys as well as for land-atmosphere exchanges in forest landscapes.